2015
DOI: 10.5551/jat.26823
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Statins on the Kidney Function in Patients with Type 2 Diabetes

Abstract: Aim:Whether there are differences among statins in their effect on the kidney function in diabetic patients remains controversial. In this report, we aimed to examine the comparative effects of statins on the kidney function in a long-term follow-up study. Methods: This was a single-center longitudinal observational historical cohort study. We enrolled 326 Japanese adult ambulatory patients with type 2 diabetes who were newly prescribed one of four statins (pravastatin, rosuvastatin, atorvastatin and pitavasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The bene cial effects of pravastatin on renal function reported in this study supports with the ndings of previous studies [11,12,22,23]. A post-hoc, large-scale RCT reported that patients with moderate CKD who received pravastatin therapy showed an increase in eGFR (+ 6.3%) [22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The bene cial effects of pravastatin on renal function reported in this study supports with the ndings of previous studies [11,12,22,23]. A post-hoc, large-scale RCT reported that patients with moderate CKD who received pravastatin therapy showed an increase in eGFR (+ 6.3%) [22].…”
Section: Discussionsupporting
confidence: 90%
“…These ndings suggest that use of pravastatin in patients with dyslipidemia and T2DM may provide better renal function than the use of other statins. A Japanese longitudinal cohort study reported that pravastatin outperformed rosuvastatin, atorvastatin, and pitavastatin in preserving renal function in patients with T2DM [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported that pravastatin improved kidney function in patients with moderate-to-severe kidney disease [12,13]. A post-hoc analysis of three RCTs conducted in the USA, UK, Scotland, and Australia reported that pravastatin was associated with a 34% decrease in the rate of kidney function loss.…”
Section: Statinsmentioning
confidence: 98%
“…In this sense, recent evidences indicate that not all statins display the same renal safety profile (progression of the CKD and/or effects on albumin/proteinuria) [28]. The selection of a statin in renal patients with nephropathy whether associated with diabetes or not [21,29], must guarantee its safe use. This does not seem to be always considered by prescribing practitioners [30].…”
Section: Sci Forschenmentioning
confidence: 99%